(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The collection and analysis of the beneficial properties of a medicinal plant is the basis for the creation of dosage forms with new pharmacological activity. The medicinal plant we are studying, chamomile pharmacy, has been used in traditional medicine for a long time. Today’s medicine and pharmacy requires precision in research. Materials and methods of research. The materials of this article are a review of sources about chamomile pharmacy, which is used as a promising tool in dentistry.